Princípio da fungibildiade recursal: hipóteses de aplicação no CPC/2015 - Carvalho, Vinícius Bellato Ribeiro de (2021)
The central object of this work is the study of the principle of appeal fungibility, focusing on some hyphoteses of applicatio in CPC/2015. However, before going into the central theme of this work, we will present some concepts of principle and point out the concept that most closely matches the sense used to refer to the principle of appeal fungibility. In order to carry out this study, we will also analyze other principles of the general theory of appeals, as well as the appeal admissibility requirements. In sequence, we will analyze the outlines of the principle of appeal fungibility, defining its incidence requirements. Finally, based on the assumptions established in the analysis of the appeal system and the analysis of the requirements for the application of the principle of appeal fungibility, we will enter the central object of this work, the hypotheses of application of the principle in question in CPC/2015. When examining the central theme of this work, we conclude, without excluding other situations, that the principle of fungibility must focus on: i) when an appeal or interlocutory appeal is filed against the decision that judges and ends the liquidation phase; ii) when an appeal or an interlocutory appeal is filed against the decision judging the first phase of the action to demand accounts; iii) when the party uses some means of challenge against the decision to dismiss the appeal against an internal appeal filed against the decision that denies the continuation of an extraordinary appeal or a special appeal, based on art. 1,030, I, a) or b), of CPC/2015